Implementing Effective Measures for Preventing the Concealment of Criminal Offenses by the Police as a Guarantee of National Security - BEKISHEV, Askhat K.; KAN, Aleksandr G.; IBRAYEVA, Alua S.; DYUSSEBALIYEVA, S. S.; IBRAYEV, Nurlan Salamatovich (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019DO - 10.14505//jarle.v10.3(41).03, 2019)
The research dwells upon the issues of considering citizens' appeals by police officers, in particular, preventing the concealment of criminal offenses. The authors of the article have comprehensively investigated possible ways of concealing criminal offenses and proposed some measures for preventing such violations. They have also analyzed the information technologies used by internal affairs bodies in operational activities both in the Republic of Kazakhstan and in other countries. The measures developed by the authors comprise the introduction of a new method of submitting citizens' appeals to the police, remote monitoring of the procedure for considering citizens' appeals and the modernization of the existing police stations and police dispatch centers. According to the results of a sociological survey, the above-mentioned measures can timely restrain police violations, respond to citizens' appeals and promptly disclose criminal offenses, thereby improving publicconfidence in police officers.